Recent advances in the pretreatment of lignocellulosic biomass for enhanced biofuel production - Yildirim, Oznur; Songur, Rahime; Bayraktar, Emine; Demir, Ahmet; Ozkaya, Bestami (INDERSCIENCE ENTERPRISES LTD, 2020)
Lignocellulosic biomass has a hard matrix consisting of cellulose, hemicellulose, and lignin, which stores carbon and chemical energy in its structure. Although its structure is resistant to biodegradation, it should be considered as an important raw material of high added value products such as ethanol and butanol. During the biologically refining of these products with a bio-refinery approach, it is essential to breakdown this structure with pre-hydrolysis. Therefore, the optimisation and feasibility of biological processes strictly depend on the pretreatment step. This study aimed to contribute to ensuring accelerated biofuel production by examining all the applications adopted for the preliminary hydrolysis process in recent years. Another considerable point is being to release toxic compounds from the degradation of hemicellulose and cellulose during the pretreatment step, which is one of the discussed key points in this study. This study set out the challenges and implications in the pretreatment step of lignocellulosic biomass, which will contribute to the commercialisation of the biotransformation systems refining of high added value products with the biorefinery approach.
Keywords: lignocellulosic biomass; pre-hydrolysis; toxicity; bio-ethanol; bio-butanol; biomethane; biohydrogen; BUTANOL-ETHANOL PRODUCTION; HYDROGEN-PRODUCTION; ENZYMATIC SACCHARIFICATION; METHANE PRODUCTION; ACID PRETREATMENT; ABE FERMENTATION; RUMEN FLUID; SACCHAROMYCES-CEREVISIAE; BIOETHANOL PRODUCTION; ANAEROBIC-DIGESTION; Environmental Sciences & Ecology